Síndrome de Bernard-Soulier, pruebas de laboratorio y características clínicas. - Acosta Aldas, Diana Carolina (2025)
Bernard-Soulier syndrome is a rare inherited bleeding disorder caused by a deficiency of the GPIb-IX-V complex, the primary receptor for von Willebrand factor, which is essential for platelet adhesion. The condition is primarily characterized by the presence of macroplatelets and thrombocytopenia. The objective of this project was to investigate the clinical features and laboratory tests used to diagnose this condition through a literature review. The study employed a qualitative approach with a descriptive, non experimental, cross-sectional, and retrospective design. Information was gathered from various databases, including PubMed, SciELO, Elsevier, Blood Research, among others. A total of 30 articles were selected from an initial pool of 52 references, based on defined inclusion and exclusion criteria. Findings indicated that age is not a significant factor in the manifestation of this disease. The most common symptoms reported were epistaxis (25%), gingival bleeding (22.5%), and menorrhagia (17.5%), followed by other manifestations such as hematomas and gastrointestinal bleeding. The most frequently used diagnostic tests included complete blood count (16.9%), peripheral blood smear (16.9%), platelet aggregation studies (18%), and flow cytometry (14.4%). Key diagnostic findings associated with Bernard-Soulier syndrome include macrothrombocytopenia, glycoprotein Ib complex deficiency, and impaired ristocetin induced platelet aggregation. In conclusion, the accurate identification of clinical manifestations, combined with the appropriate laboratory tests, is essential for the timely and effective diagnosis of Bernard-Soulier syndrome.